Aminoacylase 1 deficiency: case report on three affected siblings - Smolka, Vratislav; Friedecky, David; Kolarova, Jana; Tkacik, Oksana; Foltenova, Hana; Bekarek, Vojtech; Vrtel, Petr; Srovnal, Josef (AME case reports, 2024)
BACKGROUND: Aminoacylase 1 (ACY1, EC 3.5.1.14) deficiency (ACY1D) is a very rare inherited metabolic disease (IMD) with autosomal recessive inheritance (OMIM #609924). Up to date, only 15 cases have been reported in the literature. It is diagnosed by detecting acetylated amino acids among the patient's urine organic acids by gas chromatography-mass spectrometry. Its clinical manifestations are highly variable, ranging from severe neurological symptoms to being asymptomatic. CASE DESCRIPTION: We present a 14-year-old boy with mild intellectual disability, speech sound disorder and non-alcoholic fatty liver disease who exhibited increased urinary excretion of N-acetylalanine, N-acetylmethionine and N-acetylglutamine during testing for inherited metabolic disorders. A suspected ACY1D was subsequently confirmed by targeted next generation sequencing, which revealed the presence of a homozygous pathogenic missense mutation in the ACY1 gene, c.1057C>T (p.Arg353Cys). The proband underwent speech education with good outcome. The same homozygous mutation in ACY1 gene was found in the boy's two brothers, who exhibited slightly varied intellectual abilities. Follow-up examinations of the siblings revealed no deterioration in their mental skills. CONCLUSIONS: These results suggest that uneven mental abilities in pediatric patients with various disorders including autism spectrum disorder may be sufficient grounds to warrant metabolic testing for ACY1D. The acylglycines urine excretion could be a promising novel metabolic marker for ACY1D testing.